Hey there Titachely1p09ewg,
Answer:
7d + d = 7 (9) + 9
= 63 + 9
= 72
Hope this helps :D
<em>~Natasha♥</em>
Answer:
6
Step-by-step explanation:
Set the equations equal to each other
Subtract x from both sides
Divide both sides by -4
x=-1/2
Old fndkld vnds lfksiocldk c
Answer:
He set the factored expressions equal to each other. instead of setting them equal to zero
Step-by-step explanation:
f(x) = x^2 + 4x + 3. His work is shown below.
0 = x^2 + 4x + 3
0 = (x + 3)(x + 1)
Here is where we use the zero product property
x+3 = 0 x+1 =0 We do not set them equal to each other